ChemInform Abstract: A New Furfural Diglycoside and Other Carbohydrate Derivatives from Fermented Beverage of Prunus mume Fruit. Issue 2 (January 2015) - Yan, Xi‐Tao; Li, Wei; Sun, Ya‐Nan; Yang, Seo Young; Song, Gyu Yong; Kim, Young Ho
Abstract isolation and structure determination of the new furfural diglycoside (I) along with 18 known compounds